Blastomyscosis Acquired by Three Children in Toronto - Stacey Bernstein; Hermine I Brunner; Richard Summerbell; Upton Allen; Paul Babyn; Susan E Richardson (Canadian Journal of Infectious Diseases)
Three paediatric cases of blastomycosis, apparently acquired in or near Toronto, Ontario, a region not known to be endemic for this disease, are described. Blastomycosis was not suspected clinically in any of the three cases, and the diagnosis was established only when the diagnostic net was broadened to include fungal and mycobacterial cultures. All three patients were diagnosed after significant delays, which is consistent with the rarity of the disease in children and its acquisition outside previously accepted geographical boundaries. Pulmonary involvement was present in all three children, while one also had multifocal osteomyelitis. Drug therapy was successful in all three cases, either with amphotericin B followed by itraconazole, or itraconazole alone. Blastomycosis should be included in the differential diagnosis of a patient from the Toronto area who presents with a compatible history despite a negative travel history to known endemic zones.